Plasmid Role in Crystals Protein Production in Locally Isolated Bacillus Thuringiensis - Jaafar, Mohammad; Al-Kazaz, Abdul Kareem; Mohammad, Ali (Iraqi Journal of Science, 2024)
The ability of crystals protein production was studied in local isolate Bacillusthuringiensis by microscope examination, and the crystals protein production were seenafter 48 hour from growth starting, the study of plasmid profile of the isolate using gelelectrophoresis technique in 0.7% of agaros gel, revealed that it had one Mega plasmidband, the plasmid role in production of crystals protein was studied by using conjugation experiments, that they applied on the local isolate B. thuringiensis which was crystalsprotein producer and Rifamycin sensitive as donor cells, with Bacillus spp. which didn’tproduce crystals protein and Rifamycin resistance as recipient cells. Conjugationexperiments assured the transmission of crystals production trait with Plasmid to therecipient cells, this result confirmed that crystals protein trait was Plasmid bourn.